The Impact of Body Mass Index on Postpartum Infectious Morbidities and Wound Complications: A Study of Extremes - Sheikh, Iqra; Fuller, Kylie A.; Addae-Konadu, Kateena; Dotters-Katz, Sarah K.; Varvoutis, Megan S. (American Journal of Perinatology, 2021)
Objective As body mass index increases, the risk of postpartum infections has been shown to increase. However, most studies lump women with a body mass index (BMI) of above 40 kg/m2 together, making risk assessment for women in higher BMI categories challenging. The objective of this study was to evaluate the impact of extreme obesity on postpartum infectious morbidity and wound complications during the postpartum period.Study Design The present study is a secondary analysis of women who underwent cesarean delivery and had BMI ≥ 40 kg/m2 in the Maternal-Fetal Medicine Units Cesarean Registry. The primary outcome was a composite of postpartum infectious morbidity including endometritis, wound infection, inpatient wound complication prior to discharge, and readmission due to wound complications. Appropriate statistics used to compare baseline demographics, pregnancy complications, and primary outcomes among women by increasing BMI groups (40–49.9, 50–59.9, 60–69.9, and >70 kg/m2).Results Rates of postpartum infectious morbidity increased with BMI category (11.7% BMI: 50–59.9 kg/m2; 13.7% BMI: 60–69.9 kg/m2; and 21.9% BMI >70+ kg/m2; p = 0.001). Readmission for wound complications also increased with BMI (3.1% for BMI: 50–59.9 kg/m2; 6.2% for BMI: 60–69.9 kg/m2; and 9.4% for BMI >70+ kg/m2; p = 0.001). After adjusting for confounders, increased BMI of 70+ kg/m2 category remained the most significant predictor of postpartum infectious complications compared with women with BMI of 40 to 49.9 kg/m2 (adjusted odds ratio [aOR] = 6.38; 95% confidence interval [CI]: 1.37–29.7). The adjusted odds of readmission also increased with BMI (aOR = 2.33, 95% CI: 1.35–4.02 for BMI 50–59.9 kg/m2; aOR = 4.91, 95% CI: 2.07–11.7 for BMI of 60–69.9 kg/m2; and aOR = 36.2, 95% CI: 7.45–176 for BMI >70 kg/m2).Conclusion Women with BMI 50 to 70+ kg/m2 are at an increased risk of postpartum wound infections and complications compared with women with BMI 40 to 49.9 kg/m2. These data provide increased guidance for counseling women with an extremely elevated BMI and highlight the importance of postpartum wound prevention bundles.Key Points
Keywords: postpartum infection; morbid obesity; cesarean; wound infection